Strategi Komunikasi Pemasaran Instagram Dalam Meningkatkan Brand Awareness Di Glow Wedding and Event Planner - Fatiha, Putri Salaisya; Suprastayasa, I Gusti Ngurah Agung; Swandewi, Ni Kadek (Journal of Event and Convention Management, 2025)
In the ever evolving digital era, social media plays an important role in building communication between business actors and consumers. Glow Wedding and Event Planner needs to adopt the right digital marketing strategy in order to survive and compete in an increasingly competitive market. This study uses a qualitative approach with interview,observation, and documentation methods, and is analyzed through a SWOT framework to identify the company's strengths, weaknesses, opportunities, and threats. The SWOT analysis shows that Glow Wedding and Event Planner has strengths in the form of professional services and creative decorations. External opportunities that can be utilized include thematic wedding trends and the high use of social media by potential consumers.The SO (Strength-Opportunity) strategy focuses on strengthening branding by utilizing attractive visual content and client testimonials. However, the company also faces weaknesses such as a lack of experts in digital marketing. The WO (Weakness-Opportunity) strategy can be implemented by recruiting competent social media admins and providing ongoing training. Facing threats from competitors and changes in digital trends, Glow can implement the ST (Strength-Threats) strategy through service innovation and maintaining quality consistently. Meanwhile, the WT (Weakness-Threats) strategy involves improving internal management and evaluating marketing strategies regularly. Optimizing Instagram features such as Stories, Reels, Feeds, and Ads is an important step in building broad interactions with the audience and increasing Glow Wedding and Event Planner's competitiveness in the wedding and event planning industry. With the right strategy, Glow can increase brand visibility, reach new markets, and strengthen customer loyalty in the long term.